Heterogeneous macro and financial effects of ECB asset purchase programs - Terri van der Zwan; Erik Kole; Michel van der Wel (Tinbergen Institute, 2021)
Central banks resorted to asset purchase programs to replace conventional policy measures, which became ineffective after interest rates approached the zero lower bound. We investigate their effects on financial markets and focus on heterogeneous transmission using a Bayesian structural vector autoregression analysis. Since financial markets react directly to policy announcements, we base our identification scheme on market surprises at the announcement time. We find evidence of a stimulating effect on the economy, declining government bond yields, increasing stock prices, increasing value-growth spread and a reduction in stress in corporate and sovereign debt markets after an asset purchase shock. We disentangle the effect among industry sectors and EMU countries and find that the effect is heterogeneous, with financial stocks and the economy of Southern European countries being the most positively affected.
Keywords: E44; E52; E58; F37; G15; 330; Unconventional monetary policy; financial markets; heterogeneity; structural vector autoregression